1985
DOI: 10.1002/bjs.1800720915
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of mucinous colorectal carcinoma

Abstract: The clinical and pathological features of 54 mucinous carcinomas of the large intestine were compared with those of 576 non-mucinous carcinomas. Tumours were only categorized as mucinous if they contained at least 60 per cent of mucin by volume. Those with a moderate mucin content (60-80 per cent) were indistinguishable in behaviour from 'non-mucinous' tumours. By contrast, those with a high mucin content (greater than 80 per cent) showed several differences from non-mucinous cancers: they had a more proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
91
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 12 publications
11
91
0
4
Order By: Relevance
“…In contrast, mucinous adenocarcinoma is characterized by abundant extracellular mucin produced by tumor cells. Mucinous adenocarcinoma shares some clinical characteristics with signetring cell carcinoma, such as affecting younger patients, 4,5 lymph node metastases, 2 and advanced stage at presentation. 2,4,5 Both colorectal mucinous adenocarcinoma and signet-ring cell carcinoma are associated with high-frequency microsatellite instability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, mucinous adenocarcinoma is characterized by abundant extracellular mucin produced by tumor cells. Mucinous adenocarcinoma shares some clinical characteristics with signetring cell carcinoma, such as affecting younger patients, 4,5 lymph node metastases, 2 and advanced stage at presentation. 2,4,5 Both colorectal mucinous adenocarcinoma and signet-ring cell carcinoma are associated with high-frequency microsatellite instability.…”
mentioning
confidence: 99%
“…Mucinous adenocarcinoma shares some clinical characteristics with signetring cell carcinoma, such as affecting younger patients, 4,5 lymph node metastases, 2 and advanced stage at presentation. 2,4,5 Both colorectal mucinous adenocarcinoma and signet-ring cell carcinoma are associated with high-frequency microsatellite instability. [6][7][8] We also believe that there are clinicopathological differences between mucinous adenocarcinomas and signet-ring cell carcinomas, especially in the aggressiveness of biological behavior.…”
mentioning
confidence: 99%
“…8 The prognosis of CRC mucinous tumors is more controversial, and some studies have reported a worse outcome for these tumors. 9 Although several studies have shown histology to be an important factor in CRC, few have fully characterized this variable at the population level. In this study, we provide detailed histology data for CRC cases diagnosed in the U.S. from 1998-2001.…”
mentioning
confidence: 99%
“…Nos pacientes com displasia de alto grau, o diagnóstico sendo confirmado por mais de um patologista experiente, está indicada a ressecção cirúrgica do órgão. Entretanto, outros autores recomendam a 21 demonstraram que uma das características importantes dos tumores de cólon seria a sua capacidade de produção de muco, que estaria relacionada com o comportamento biológico da neoplasia. E durante muitos anos os carcinomas mucinosos, que representam de 15 a 20% dos carcinomas coloretais, foram considerados os de pior prognóstico, apresentando taxas elevadas de recorrência e baixas de sobrevida, principalmente quando o componente mucinoso do tumor ocupava mais de 60% do seu volume.…”
Section: Discussão Esôfago De Barrett E Adenocarcinomaunclassified